Geochemical Modeling of CO2-Brine Gabbro-diorite Interaction for in-situ Mineral Carbonation - Abdoulghafour, H (2021)
This work consists of a geochemical modeling applied to in situ mineral carbonation. The simulations are based on previous laboratory tests that followed 4 time sets of a plutonic mafic rock samples immersed into supercritical CO2 – brine (8 MPa and 40°C) up to a maximum of 64-days. The study aims to mimic the experimental results; pH evolution, solution concentration changes and newly formed mineral phases. Three simulations were conducted using Crunchflow simulator, emphasizing the key role of the specific surface area on the reaction rate. The simulations corroborate the experimental results until 64-days, that is, a dominant dissolution process. Beyond the observed time, the simulation predicted the concentration breakthrough induced by secondary mineral formation. Zeolites and clay minerals are the first phase to form, competing with carbonates after 65- days. The simultaneous competition of silicate minerals to fix Calcium ions can limit carbonates formation reducing the potential for CO2 sequestration by mineral carbonation in mafic rocks.